Activation of the G Protein-Coupled Estrogen Receptor Elicits Store Calcium Release and Phosphorylation of the Mu-Opioid Receptors in the Human Neuroblastoma SH-SY5Y Cells - Ding, Xiaowei; Gao, Ting; Gao, Po; Meng, Youqiang; Zheng, Yi; Dong, Li; Luo, Ping; Zhang, Guohua; Shi, Xueyin; Rong, Weifang (Frontiers in Neuroscience, 2019)
Estrogens exert extensive influences on the nervous system besides their well-known roles in regulation of reproduction and metabolism. Estrogens act via the nuclear receptor ERα and ERβ to regulate gene transcription (classical genomic effects). In addition, estrogens are also known to cause rapid non-genomic effects on neuronal functions including inducing fast changes in cytosolic calcium level and rapidly desensitizing the μ type opioid receptor (MOR). The receptors responsible for the rapid actions of estrogens remain uncertain, but recent evidence points to the G protein-coupled estrogen receptor (GPER), which has been shown to be expressed widely in the nervous system. In the current study, we test the hypothesis that activation of GPER may mediate rapid calcium signaling, which may promote phosphorylation of MOR through the calcium-dependent protein kinases in neuronal cells. By qPCR and immunocytochemistry, we found that the human neuroblastoma SH-SY5Y cells endogenously express GPER and MOR. Activation of GPER by 17β-estradiol (E2) and G-1 (GPER selective agonist) evoked a rapid calcium rise in a concentration-dependent manner, which was due to store release rather than calcium entry. The GPER antagonist G15, the PLC inhibitor U73122 and the IP3 receptor inhibitor 2-APB each virtually abolished the calcium responses to E2 or G1. Activation of GPER stimulated translocation of PKC isoforms (α and ε) to the plasma membrane, which led to MOR phosphorylation. Additionally, E2 and G-1 stimulated c-Fos expression in SH-SY5Y cells in a PLC/IP3-dependent manner. In conclusion, the present study has revealed a novel GPER-mediated estrogenic signaling in neuroblastoma cells in which activation of GPER is followed by rapid calcium mobilization, PKC activation and MOR phosphorylation. GPER-mediated rapid calcium signal may also be transmitted to the nucleus to impact on gene transcription. Such signaling cascade may play important roles in the regulation of opioid signaling in the brain.